Enhanced lipid production in thermo-tolerant mutants of Chlorella pyrenoidosa NCIM 2738. (December 2016) - Sachdeva, Neha; Gupta, Ravi Prakash; Mathur, Anshu Shankar; Tuli, Deepak Kumar
Highlights: Two thermo-tolerant mutants of Chlorella pyrenoidosa were developed. Both mutants showed >50% increase in lipid content over wildtype. Mutants could survive at temperature up to 47 °C. PAM Flurometry and cellular techniques evaluated reasons behind marked increase. Abstract: The present study aimed to develop thermo-tolerant mutants of Chlorella pyrenoidosa NCIM 2738 for high lipids production. For this, ethyl methane sulfonate was used, which generated two effective thermo-tolerant mutants, M18 and M24 of Chlorella pyrenoidosa NCIM 2738, capable of surviving at temperature up to 47 °C and showing improved lipid and biomass yields. They showed 59.62% and 50.75% increase, respectively in lipid content compared to wild type at 30 °C, which could not grow at temperature above 35 °C. The novelty of this study lied in incorporation of PAM Flurometry with mutagenesis to generate thermo-tolerant mutants of C. pyrenoidosa and investigating the reasons for increased yields of mutants at cellular and photosynthetic levels with the aim to use them for commercial biodiesel production.